Actividades lúdicas y su incidencia en el aprendizaje cognitivo en los niños de subnivel II de la Unidad Educativa “Dr. Lorenzo Rufo Peña” - Arana Cedeño, Nathaly Silvana (2023)
The present research focused on analyzing the incidence of recreational activities on the cognitive learning of children in sublevel II in the "Dr. Lorenzo Rufo Peña" Educational Unit. A mixed research approach was used, combining qualitative and quantitative methods. The research design was non-experimental, with a documentary and descriptive scope. The information was collected through a survey applied to teachers and representatives of children in sublevel II, based on a Likert scale. The results demonstrated a positive perception of the participants towards recreational activities, highlighting their ability to stimulate children's concentration. Furthermore, the importance of cognitive learning from an early age in the school context was recognized. In conclusion, this study highlights the fundamental role of recreational activities in the development of cognitive learning of children in sublevel II. The training of teachers and representatives is recommended to optimize the impact of these activities in the educational and family environment, as well as the integration of practices that promote cognitive development in the educational curriculum.